2014
DOI: 10.1039/c4cp01394h
|View full text |Cite
|
Sign up to set email alerts
|

Superbasicity of silylene derivatives achieved via non-covalent intramolecular cation⋯π interactions and exploited as molecular containers for CO2

Abstract: We have reported for the first time designed silylene superbases involving intramolecular H(+)···π interaction using density functional theory (DFT) calculations. The non-covalent interactions augment the proton affinity values by 13 kcal mol−1 in the designed superbase (1) compared to the acyclic silylene, [:Si(NMe2)2]. These divalent Si(II) compounds can act as powerful neutral organic superbases in gas and solvent phases. The DFT calculations performed at the B3LYP/6-311+G**//B3LYP/6-31+G* level of theory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 127 publications
0
21
0
Order By: Relevance
“…[13] More recently different innovative bases have been proposed, such as cyclopropeneimines [14] and silylene bases. [15] Despite av ast range of potential applications, [1] many classes of superbases (guanidino proton sponges, [7] phosphorus ylides [16] )a re still almost unexplored.An early Minireview by Schwesinger [17] summarizes the principal approaches to enhancing the basicity of organosuperbases:1 )the "battery cell" principle, [3] that is,s tepwise expansion of the molecular scaffold by forming alternating formal single and double bonds and thereby enhancing the structure where the positive charge can be delocalized (Scheme 1);2 )stabilization of the protonated form by intramolecular hydrogen bond (chelation);a nd 3) structures that become aromatic on protonation. It was concluded that the most fruitful approach to design of superbases is the battery cell principle.T he best known practical example is the phosphazene family of superbases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13] More recently different innovative bases have been proposed, such as cyclopropeneimines [14] and silylene bases. [15] Despite av ast range of potential applications, [1] many classes of superbases (guanidino proton sponges, [7] phosphorus ylides [16] )a re still almost unexplored.An early Minireview by Schwesinger [17] summarizes the principal approaches to enhancing the basicity of organosuperbases:1 )the "battery cell" principle, [3] that is,s tepwise expansion of the molecular scaffold by forming alternating formal single and double bonds and thereby enhancing the structure where the positive charge can be delocalized (Scheme 1);2 )stabilization of the protonated form by intramolecular hydrogen bond (chelation);a nd 3) structures that become aromatic on protonation. It was concluded that the most fruitful approach to design of superbases is the battery cell principle.T he best known practical example is the phosphazene family of superbases.…”
mentioning
confidence: 99%
“…[13] More recently different innovative bases have been proposed, such as cyclopropeneimines [14] and silylene bases. [15] Despite av ast range of potential applications, [1] many classes of superbases (guanidino proton sponges, [7] phosphorus ylides [16] )a re still almost unexplored.…”
mentioning
confidence: 99%
“…Such materials can also be used for the separation of CO 2 and CO gas mixture . CO 2 separation from the flue gas of coal‐burning power plants can be work as one of the solution for managing CO 2 emission in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Such materials can also be used for the separation of CO 2 and CO gas mixture. [35,36] CO 2 separation from the flue gas of coalburning power plants can be work as one of the solution for managing CO 2 emission in the atmosphere. Graphene, graphene derivatives [37] and lithium doped materials [38][39][40] are extensively studied for CO2 adsorption process.…”
mentioning
confidence: 99%
“…[48] They have been used in many applications such as catalysis in organic reactions, diabetes medication,g ene therapy,c apture of CO 2 , and conversiont ou seful materials. [49][50][51][52][53][54]60] Therefore,d esign of novel superbasic molecules is an active area of research.M any new classes of nonionics uperbases have been designed and preparedd uringt he past decades, such as guanidinophosphazenes,s uperbasic guanidine derivatives, chiral phosphazenes, quinones,p hosphonium ylides, and azap hosphatranes. [55][56][57][58] The basicities of carbenes have been found to be higher than normal nitrogen containing organic bases [56,59] and their basicity has also been examined within the conceptual framework of non-covalent interactions with p-systems.…”
Section: Introductionmentioning
confidence: 99%